Neutralizing monoclonal antibodies for COVID-19 treatment and prevention - Jaworski, Juan Pablo (2020)
The SARS-CoV-2 pandemic has caused unprecedented global health and economic crises. Several vaccine approaches and repurposed drugs are currently under evaluation for safety and efficacy. However, none of them have been approved for COVID-19 yet. Meanwhile, several nMAbs targeting SARS-CoV-2 spike glycoprotein are in different stages of development and clinical testing. Preclinical studies have shown that cocktails of potent nMAbs targeting the receptor binding site of SARS-CoV-2, as well as broad-nMAbs targeting conserved regions within the virus spike, might be effective for the treatment and prophylaxis of COVID-19. Currently, several clinical trials have started to test safety, tolerability, PKs and efficacy of these nMAbs. One paramount limitation for the use of nMAbs in clinical settings is the production of large amounts of MAbs and the high costs related to it. Cooperation among public and private institutions coupled with speed of development, rapid safety evaluation and efficacy, and early planning for scale-up and manufacture will be critical for the control of COVID-19 pandemic